Mobile-assisted phonological training: Improving Indonesian EFL students’ intelligibility in academic communication - Shaumiwaty Shaumiwaty; Sholihatul Hamidah Daulay; Yunie Amalia Rakhmita; Dardanila Dardanila (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
The growing demand for digital-based education in the 21st century highlights the need for innovative pronunciation teaching that supports clearer and more accessible academic English. Thus, this study investigated the effectiveness of mobile-assisted audio training in improving Indonesian EFL students' speech intelligibility in academic communication. Using a quasi-experimental pretest-posttest control group design, the study involved 60 twelfth grade students at SMA Negeri 1 Aceh Besar, equally divided into an experimental group and a control group. The experimental group received mobile-based audio training, while the control group received traditional pronunciation training. Data were collected through speech intelligibility tests, pronunciation accuracy rubrics and student perception questionnaires. Statistical analyzes including descriptive statistics, paired samples t-test, independent samples t-test and ANCOVA were performed using SPSS. The findings revealed a significant improvement in the intelligibility scores of the experimental group compared to the control group. In addition, the questionnaire results indicated that students in the experimental group reported higher levels of motivation, engagement, and positive perceptions toward mobile-assisted phonological training compared to the control group. The study emphasizes the pedagogical potential of integrating mobile technology into EFL pronunciation teaching in Indonesian secondary schools.